THE EFFECTS OF SUCCESSIVE THINNINGS ON THE HYPSOMETRIC FUNCTION FOR Pinus oocarpa STANDS - Machado, Sebastião do Amaral; Barros, Dalmo Arantes de; Scolforo, José Roberto Soares; Acerbi Junior, Fausto Weimar (Floresta, 2011)
<!--[if !mso]> <mce:style><! v\:* {behavior:url(#default#VML);} o\:* {behavior:url(#default#VML);} w\:* {behavior:url(#default#VML);} .shape {behavior:url(#default#VML);} --> <!--[endif] --><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if !mso]> <mce:style><! v\:* {behavior:url(#default#VML);} o\:* {behavior:url(#default#VML);} w\:* {behavior:url(#default#VML);} .shape {behavior:url(#default#VML);} --> <!--[endif] --><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if !mso]> <mce:style><! v\:* {behavior:url(#default#VML);} o\:* {behavior:url(#default#VML);} w\:* {behavior:url(#default#VML);} .shape {behavior:url(#default#VML);} --> <!--[endif] --><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->This research aimed to test the hypothesis that successive thinnings mischaracterize the hypsometric function, and that after some thinnings the average height of the plots or of the stand ( ) is an unbiased estimate of the remaining tree heights (hi), that is, ĥi = . The data were obtained from Duraflora S. A. in Agudos, State of São Paulo. This data set came from the measurement of diameters and respective heights of 1,100 trees equitably distributed in 11 different treatments with ages ranging from 5 to 25 years, and number of thinnings varying between 0 (zero) and 6. The Stoffels model, previously fitted to all treatments, was used to observe the behavior of the following factors: coefficient of multiple determination (R²), standard error of estimate in percent (Syx %), distribution of residuals, and the significance of the b0 and b1 coefficients in each one of the equations. After tests it was confirmed the hypothesis that average height is a precise estimate of hi for the oldest treatments with more than 4 thinnings. This means low Syx % and unbiased estimates, that is, good distribution of residuals. Keywords: Hypsometric curves; management regimes; plantations; Pinus oocarpa. Resumo Efeitos de desbastes sucessivos sobre a função hipsométrica em povoamentos de Pinus oocarpa Shiede. Esta pesquisa teve como objetivo testar a hipótese que desbastes sucessivos descaracterizam a função hipsométrica e que após alguns desbastes a altura média da parcela ou do povoamento ( ) é uma boa estimativa das demais alturas (ĥi), isto é, ĥi = . A base de dados utilizada para testar a hipótese formulada proveio de plantios de Pinus oocarpa, pertencentes à empresa Duraflora S.A., situada no município de Agudos, sudoeste do Estado de São Paulo. Esta base consistiu da altura e diâmetro de 1100 árvores distribuídas igualmente em 11 tratamentos, com variação de idades e número de desbastes. Visando atingir aos objetivos, foi primeiramente ajustado o modelo de Stoffels, separadamente para cada um dos 11 tratamentos, com o fim de observar a tendência dos coeficientes de determinação múltiplos (R2), do erro padrão da estimativa em porcentagem (Syx %), a distribuição dos resíduos e a significância dos coeficientes de interseção (b0) e de inclinação (b1) em cada uma das equações. Após proceder as análises conclui-se que a medida que se aumenta o número de desbastes os R² vão se tornando cada vez mais baixos , porém os Syx % foram sempre inferiores a 10%. Palavras-chave: Curva hipsométrica; regimes de manejo; plantações; Pinus oocarpa.